Analysis of The Application of Scientific Methods in Learning to Academic Success Skills - Motlan; Sinuraya, Jurubahasa; Sinulingga, Karya (Advances in Social Sciences Research Journal, 2019)
This study is aimed to analysis of the application of scientific methods in learning to academic success skills. Academic success skills are based on three broad research reviews that identify the critical skills needed for students to be academically and socially successful. These key skill sets include: (a) cognitive and meta-cognitive skills such as goal setting, monitoring progress, and memory skills; (b) social skills such as interpersonal, social problem solving, listening skills, and teamwork; and (c) self-management skills. In improving the skills of academic success many problems are faced. Problems can occur due to several factors including namely, concentration and memory. Scientific method which is intended to provide understanding to students in knowing, understanding various materials using a scientific approach, that information can come from anywhere, anytime, does not depend on unidirectional information. The study design was conducted on a quasi-experimental basis with 2 samples. One sample is applied scientific methods in learning that are designed along with learning tools that have been adjusted. The sample applied by the scientific method is an experimental class compared to the control class. Academic success skills are the dependent variable of the application used. The products implemented are very effective in improving the intended learning outcomes. The intended learning outcome is Academic Success Skills. This increase occurs because the design of objectives in the preparation of performance indicators is actually carried out by considering and formulating it in full. In this achievement also evidenced by a learning video that has shown every planned stage goes according to the learning device that has been prepared. In addition, improvements in each learning activity need to be constantly updated and adjusted to the characteristics of students’ learning styles. Good learning management will trigger the results of good learning outcomes in accordance with planned objectives. It also proves that learning outcomes depend on the management of learning that has been prepared.